Functional state of the myometrium of rats under chronic in vivo effect of nanostructured ZnO and ТіО2 materials - O. V. Tsymbalyuk; T. L. Davydovska; A. M. Naumenko; A. N. Liashevych; I. S. Lupaina; I. S. Voiteshenko; N. Y. Nuryshchenko; V. A. Skryshevsky (Regulatory Mechanisms in Biosystems, 2021)
The specificities of the structure and blood supply of the uterus facilitate a considerable accumulation of nanosized xenobiotics, including nanoparticles of metal oxides, in its tissues. Numerous in vitro and in vivo experiments demonstrated that nanoparticles of metal oxides (ZnO and TiO2) have significant cytotoxic activity, caused by oxidative stress induction. However, there is no information about the impact of these nanomaterials on the functional state of the myometrium under chronic exposure on the organism. Tenzometric methods and mechanokinetic analysis were used in our work to investigate the contractile activity of the myometrium of non-pregnant rats. The contractile activity was either spontaneous or induced by oxytocin (the uterotonic hormone) and acetylcholine (the agonist of muscarinic choline receptors) under chronic peroral intake of the ZnO and TiO2 aqueous nanocolloids into the organism. It was found that after burdening of rats with ZnO and ТіО2 aqueous nanocolloids there were no changes in the pacemaker-dependent mechanisms forming the frequency of spontaneous contractions in the myometrium, but there was a considerably induced increase in the AU index of contractions. It was shown that during the oxytocin-induced excitation of the myometrium under both chronic and short-term burdening of the rats with ZnO and TiO2 aqueous nanocolloids, the mechanisms that regulate the intracellular concentration of Ca2+ ions are the target for the nanomaterials. When the rats were burdened with ZnO aqueous nanocolloids for 6 months, during cholinergic excitation there was hyperstimulation of both M3-receptor-dependent mechanisms of Са2+ ions intake via the potential-governed Са2+-channels of L-type into the smooth muscles of the myometrium, and M2-receptor-dependent mechanisms, controlling the intracellular concentration of these cations. Thus, the regularities and mechanisms of the change in the functioning of uterine smooth muscles under chronic intake of the ZnO and TiO2 aqueous nanocolloids were determined in this study.